PEMINDAHAN HAK PAKAI KEPADA PIHAK LAIN DALAM PRESPEKTIF HUKUM ISLAM - Abdul Fattah; Nanda Nabila (Institut Keislaman Abdullah Faqih Gresik, 2022)
Abstract: The right of use is the right to use or collect the proceeds from something that is controlled directly by the owner of the goods, and can be transferred to another party with the permission of the owner rather than the goods to be used. In the Perspective of Islamic Law the transfer of the right of use must be with the permission of the owner of the goods that will be the object of the transfer, Imam Abu Hanifah and Ulama Malikiyah and Ulama' others argue that utilizing an item must be with the permission of the owner of the goods, if the owner of the goods does not give permission then the goods that are the object of the transfer of the right of use cannot be transferred to others. This research is a literature study (Library Research), defining literature studies is the result of literature research and the results of thinking conducted by researchers on a study. By collecting a book or reference that can be used as a relevant reference, so as to be able to get a good and correct conclusion. While judging from the type of data information this research includes qualitative research, which is research that cannot be tested with statistics. From the results of research transfer rights to other parties related to renting back rental goods, lending back loans, and renting borrowed goods according to ulma' madzhab Maliki and Madzhab Hambali punish